Increasing Students Science Process Skills and Achievement Through the Implementation of Guided Inquiry Learning Strategy of Class VIII-F SMP Negeri 5 Surakarta Class Year 2011/2012 - Alanindra Saputra; Sri Widoretno; Slamet Santoso (Universitas Sebelas Maret, 2012)
Two research objectives have been stated, namely improving student learning achievement and science process skill improvement. This two objectives were ascertained ofter the application of Guided Inquiry strategy towards junior high school student of Surakarta. This research was conducted upon junior high school student of SMP Negeri 5 Surakarta in academic year of 2011/2012. As in a classroom action research, this research performed within 4 cycles and each consist of 4 phases namely planning, action, observation and reflection. The obtained data were analized descriptively ofter validated using split half method. The result showed that Guided Inquiry did a good job. According to the observation the percentage of science process skill had been improved from the baseline 50,62% to 54,43% in 2nd cyle to 64,57% in 3rd cycle and ended up by 68,48% in the last cycle. This it can be concluded that Guided Inquiry has given effects towards science process skill student learning achievement has also been improved from baseline. The cognitive achievement has been improved from 14,53% to 15,12% in 2nd cyle to 15,75% in 3rd cycle and ended up by 15,25% in the last cycle. This improvement can also been seen in the affective and psikomotoric as well. The affective achievement has been improved from 49,96% to 51,72% in 2nd cyle to 61,07% in 3rd cycle and ended up by 61,61% in the last cycle. The Psikomotoric achievement has been improved from 43,80% to 52,01% in 2nd cyle to 62,72% in 3rd cycle and ended up by 71,93% in the last cycle. Hence it can be concluded that Guided Inquiry has considered as effective to improve learning achievement. Key Words: Guided Inquiry, Science Process Skills, Achievement